Public Health Implications of Introducing Human Papillomavirus (HPV) Vaccination in Pakistan: A protocol for a mixed-method study to explore community perceptions and health system preparedness - Khola Noreen; Samina Naeem Khalid; Mohsin Javaid; Shahzad Ali Khan (PLoS ONE, 2025)
Introduction Cervical cancer is a preventable illness, and early vaccination can serve as a primary prevention strategy. Currently, HPV vaccination has not been introduced at the national level in Pakistan, and the vaccine remains unavailable in most regions. However, efforts are underway to launch the HPV vaccination program soon. For a successful roll-out, it is essential to address circumstantial challenges and mitigate vaccine hesitancy, which stems from a complex interplay of sociocultural and contextual factors. Therefore, this study aims to comprehensively evaluate the multifaceted sociocultural, contextual, and demographic factors influencing the uptake of HPV vaccination at the community level. Objectives 1.To assess the current level of knowledge, belief, and factors associated with the acceptability of HPV vaccination among potential vaccine recipients and their parents/caregivers 2. To explore stakeholders’ perspectives on the launch of HPV vaccination, considering the dynamics of the local population in the resource-constrained country, Pakistan (OBJ 2). 3.To identify the social and behavioral factors that influence HPV vaccination acceptance and hesitancy within a local community (Punjab) (OBJ 3). Method The ethical approval of the study has been already obtained from the ethical review board of Rawalpindi Medical University (843 IREF/RMU/2024). Data will be collected after obtaining informed written consent from parents and assent from daughters. Data collection will start from April 2025 and will be completed in six months. Data compilation and results are expected by December 2025. A convergent mixed methods design will be used as it will enable the merging of qualitative and quantitative data. Data collection will involve a quantitative phase in which data will be collected from potential vaccine recipients (girls between 9–16 years) and their parents/caregivers to assess the current level of knowledge, belief, and HPV vaccine hesitancy. The qualitative phase aims to explore key stakeholders’ perspective on the health system’s preparedness and capacity for launch and uptake of HPV vaccination. The quantitative findings will be integrated with the qualitative data via the merging and expanding integration techniques to generate confirmed, expanded, and discordant meta-inferences. Discussion This study will comprehensively identify the multilevel contextual and health system factors that influence HPV vaccine uptake. This study will significantly contribute in field of Public Health by providing a foundational basis of first step of cultural adaptation and validation of BeSD tool specifically for HPV Vaccination.